AN ANALYSIS OF MARKING SYSTEM USED BY WRITING LECTURERS OF STAIN CURUP IN TESTING STUDENTS’ WRITING ABILITY - Leffi Noviyenty (P3M STAIN Kudus, 2015)
This is a descriptive study which is presented in narative way since the data is analysed by using verbal explanation. The reseracher collects the data about Writing test format, the criteria of marking and the scoring system used by Writing lecturers of STAIN Curup deeply. The subjects of this reserach are Writing Letcurers in English Tadris Study Program of STAIN Curup. A checklist and an interview guidance are used as the intruments of this research to gain the data on format of writing test and the criteria of marking. Fieldnotes are also taken in order to observe some data which is not performed in observation and also used to trianggulate the whole result. Observation, document analysis and interview are the technigues in collecting data. The finding of this research shows that Writing lecturers useGap Filling, Form Completion, Information transfer task, Letter writing, Integrating reading into Writing, Open-ended Essay Test, Responding to a given Information are their formats in testing students’ writing ability. The finding also finds that the criteria of marking used by the Writing lecturers are Grammar, Punctuation, Spelling, Relevance and Adequacy of Content. Unfortunately the writing lecturers do not include the score for each criteria. The scoring scheme is only based on the scheme designed by institusion (STAIN Curup) they are: 00 – 49 = E (gagal), 50 – 59 = D, 60 – 69 = C, 70 – 85 = B dan 86 – 100 = A.There is also no scale of scoring for each aspect of writing. It is important for writing lecturers to include the score for each criteria of marking in writing test as suggested by the theory. It can improve the objectivity of scoring and directly minimize the subjectivity. Eventhough the institution has its own regulation in calculating the score, the writing lecturers also need to consider the purpose of teaching writing skill itself.